A Multihop Clustering Algorithm for Energy Saving in Wireless Sensor Networks. (26th March 2012) - Ebadi, Saeed
Abstract : One of the important problems for wireless sensor networks is increasing the network lifetime. Clustering is an efficient technique for prolonging the lifetime of wireless sensor networks. This papers propose a multihop clustering algorithm (MHC) for energy saving in wireless sensor networks. MHC selects the clusterheads according to the two parameters the remaining energy and node degree. Also cluster heads select their members according to the two parameters of sensor the remaining energy and the distance to its cluster head. MHC is done in three phases quickly. Simulation results show that the proposed algorithm increases the network lifetime more than 16 percent compared of the LEACH protocol.